Review of Pharmacognostic Features, Phytochemical Constituents and Pharmacological Actions of Melastoma malabathricum LINN (Melastomaceae) - Suleiman, Danladi; Idris, Aliyu Masa’ud; Ibrahim, Umar Idris (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
Melastoma malabathricum is a medicinal plant found in tropical and temperate Southeast Asian countries. It has been used for a long period in traditional medicine. Moreover, various scientific investigations reported have shown that that the plant is effective against various diseases due its phytochemical constituents. This study aimed to review the studies carried on Melastoma malabathricum in order to have comprehensive information on its phytochemical constituents and pharmacological action (therapeutic uses). The data were searched from electronic data bases and some printed materials. The key word used for searching information is Melastoma malabathricum. The electronic sources of data include; highwire, googlescholar, sciencedirect and pub med. The review revealed that Melastoma malabathricum has potent therapeutic activities such as antidiabetic, antihyperlipidemic, antibacterial, antifungal, antiparasitic, antiviral, antiulcer and antidiarrheal activity. It was also reported to have antioxidant as well as hepatoprotective activity. Melastoma malabathricum contains different classes of secondary metabolites such as triterpenoid, alkaloids, amide, flavonoids anthocyanins, hydrolysable tannins and steroidal tannins. Other phytochemical constituents such as alpha –amyrin, patriscabratine, auranamide, quercetin, quercitrin, kaempferol-3-O-( 2” , 6” -di-O-p-trans-coumaroyl)-beta-glucoside, rutin, malabathrin B, C, and D. 1,2,4,6- tetra-O-galloyl-?-D-glucoside, pterocarinin C, pasuarictin, pedunculagin, 1,4,6-tri-O-galloyl-?-D-glucoside, strictinin, nobotanins B, G, H and J were isolated from M. malabathricum